Mathematical modeling of autonomous underwater vehicle propulsion and steering complex operation in oblique (beveled) water flow - Blintsov, Volodymyr; Hrudinina, Hanna (Eastern-European Journal of Enterprise Technologies, 2019)
The research of nonlinear hydrodynamic characteristics of the propulsion and steering complex (PSC), which influence the accuracy of the plane trajectory motion of an autonomous underwater vehicle (AUV), is carried out. During the underwater vehicle curvilinear motion, its PSC operates in an oblique incident water flow. This leads to a decrease in the PSC thrust force and negatively affects the controlled trajectory motion of the underwater vehicle. The research was conducted for a specific type of AUV for the plane curvilinear motion mode. The mathematical modeling method was chosen as the research method. To this end, the well-known AUV motion mathematical model is supplemented by the control system that simulates (mimics) its trajectory motion. The developed model consists of four main units: an AUV improved model; the vehicle speed setting unit; the nozzle rotation angle control unit; the unit containing the AUV pre-prepared motion trajectories. The research results of the AUV hydrodynamic parameters for several typical trajectories of its motion are presented. The investigated parameters include the following: the required nozzle rotation angle; the vehicle actual motion trajectory; the vehicle velocity; the propeller shaft moment; the propeller thrust force. As a result of the conducted researches, the dependence diagram of the propeller thrust force on the AUV nozzle rotation angle in the speed range from 0.2 m/s to 1 m/s and during the nozzle rotation in the range of up to 35° was constructed. A three-dimensional matrix, which describes the dependence of the propeller thrust force on the incident water flow angle and velocity of the vehicle, was created. The obtained dependence can be used in the synthesis of automatic control systems regulators of AUV plane manoeuvering (shunting) motion of increased accuracy.